Peningkatan Kinerja Guru Melalui Budaya Organisasi dan Kepemimpinan Servant Kepala Madrasah - Ari Kartiko; Mauhibur Rokhman; Achmad Agus Priyono; Susanto Susanto (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
Quoted from various sources, in general the performance of teachers in Indonesia is still not good, as indicated by the quality of Indonesian education based on Pisa and the results of World Bank research on education in Indonesia. So this research aims to analyze the factors that influence teacher performance by asking two research questions. The first question is how the influence of organizational culture and servant leadership of madrasah heads on teacher performance partially and simultaneously. the madrasa. The second question is which variable has the most dominant influence on teacher performance. This research uses quantitative research, with a sample of 35 people selected based on the senseu method, because the population is relatively small. The data analysis technique uses multiple linear regression analysis and the f test and t test to determine the effect partially or simultaneously. The research results show that partially and simultaneously organizational culture and servant leadership have a positive and significant influence. The variable that is more dominant in teacher performance in this research is servant leadership